2023
DOI: 10.1097/qai.0000000000003119
|View full text |Cite
|
Sign up to set email alerts
|

Male Partner Opinions of the Dapivirine Vaginal Ring Used During an Open-Label Extension HIV Prevention Trial in KwaZulu-Natal, South Africa

Abstract: Background:The dapivirine vaginal ring (“the ring”) reduced HIV acquisition by about 35% in phase III trials, with modeling from open-label extension trials estimating 50% HIV protection with consistent use. The ring may be used without male partner knowledge. The Assessment of ASPIRE and HOPE Adherence (AHA) substudy aimed to understand the impact of sociocontextual issues on ring adherence. This subanalysis provides insight into disclosure and male partner influence on ring acceptability.Methods:Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Though there is limited literature on intravaginal topical therapies for the prevention of cervical cancer in LMICs, studies on the use of intravaginal microbicides for HIV prevention among women in Sub-Saharan Africa have shown that male partner support is essential to uptake and adherence. [25][26][27] To inform feasibility studies in LMICs, we carried out a mixed-methods study in Kenya among men with active female partners to understand their knowledge of HPV and cervical cancer screening, their perspectives, and their perceived acceptability of topical, self-administered therapies for cervical precancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Though there is limited literature on intravaginal topical therapies for the prevention of cervical cancer in LMICs, studies on the use of intravaginal microbicides for HIV prevention among women in Sub-Saharan Africa have shown that male partner support is essential to uptake and adherence. [25][26][27] To inform feasibility studies in LMICs, we carried out a mixed-methods study in Kenya among men with active female partners to understand their knowledge of HPV and cervical cancer screening, their perspectives, and their perceived acceptability of topical, self-administered therapies for cervical precancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Specific to the potential use of intravaginal therapies for cervical precancer treatment, male partner support is crucial, as these therapies often require periods of abstinence during their use. Though there is limited literature on intravaginal topical therapies for the prevention of cervical cancer in LMICs, studies on the use of intravaginal microbicides for HIV prevention among women in Sub-Saharan Africa have shown that male partner support is essential to uptake and adherence [28][29][30]. To inform feasibility studies in LMICs, we carried out a mixed-methods study in Kenya among men with active female partners to understand their knowledge of HPV and cervical cancer screening, their perspectives and their perceived acceptability of topical, self-administered therapies for cervical precancer treatment.…”
Section: Introductionmentioning
confidence: 99%